IMPLEMENTASI PROGRAM D-CARDS DALAM UPAYA PENINGKATAN LAYANAN INKLUSIF DI DISPENDUKCAPIL KOTA MALANG - Annisa, Khofifah Khoiru; Muljanto, M. Agus (Universitas Djuanda, 2026)
Inclusive public services represent a fundamental right for every citizen, including people with disabilities who frequently face barriers, discrimination, and social inequalities when accessing population administration services, making this research urgent due to the need for service innovations that accommodate vulnerable groups. This study aims to analyze the implementation of the D-CARDS program to enhance inclusive services in Malang City using a qualitative descriptive approach with data collected through in-depth interviews, observation, and documentation from five informants: the Secretary of the D-CARDS innovation team, data recording staff, D-CARDS innovation team members, and two program beneficiaries, analyzed via three key aspects influencing success organization, interpretation, and application. Findings reveal suboptimal implementation: organizationally, a mobile service team exists with stakeholder collaboration, resource support, accessible units, and methods, but field staff shortages, lack of technical training, and budget constraints persist; interpretation includes technical guidelines and implementers yet lacks active socialization; application follows SOPs but encounters technical obstacles. Overall, D-CARDS proves a vital innovation for inclusive public services requiring strengthened support across all three aspects to minimize shortcomings, ensure widespread equitable benefits, enhance competent human resources, conduct comprehensive socialization, and adopt more proactive service methods to promote social justice in population administration.